2015
DOI: 10.1016/j.virol.2015.08.026
|View full text |Cite
|
Sign up to set email alerts
|

RNA helicase MOV10 functions as a co-factor of HIV-1 Rev to facilitate Rev/RRE-dependent nuclear export of viral mRNAs

Abstract: Human immunodeficiency virus type 1 (HIV-1) exploits multiple host factors during its replication. The REV/RRE-dependent nuclear export of unspliced/partially spliced viral transcripts needs the assistance of host proteins. Recent studies have shown that MOV10 overexpression inhibited HIV-1 replication at various steps. However, the endogenous MOV10 was required in certain step(s) of HIV-1 replication. In this report, we found that MOV10 potently enhances the nuclear export of viral mRNAs and subsequently incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 79 publications
1
28
0
Order By: Relevance
“…In humans, MOV10 associates with APOBEC3 proteins and components of RISC in SGs and PBs [ 156 , 228 ]. Several groups examined the role of MOV10 in limiting HIV-1 replication but results were conflicted [ 229 233 ]. However, MOV10 strongly inhibits all human non-LTR retrotransposons in cell culture, consistent with its subcellular colocalization with L1 ORF1p in cytoplasmic granules, co-immunoprecipitation (co-IP) with the L1 RNP, and binding of L1 transcripts [ 232 , 234 236 ].…”
Section: Lines Of Defensementioning
confidence: 99%
“…In humans, MOV10 associates with APOBEC3 proteins and components of RISC in SGs and PBs [ 156 , 228 ]. Several groups examined the role of MOV10 in limiting HIV-1 replication but results were conflicted [ 229 233 ]. However, MOV10 strongly inhibits all human non-LTR retrotransposons in cell culture, consistent with its subcellular colocalization with L1 ORF1p in cytoplasmic granules, co-immunoprecipitation (co-IP) with the L1 RNP, and binding of L1 transcripts [ 232 , 234 236 ].…”
Section: Lines Of Defensementioning
confidence: 99%
“…This RNA-protein interaction helps the unspliced transcript evade surveillance mechanisms for degradation 4 , 6 and facilitates its export by the alternative Rev/CRM1-dependent nuclear export pathway 7 . Furthermore, Rev has been shown to recruit host proteins of diverse functions, including; nuclear matrix protein MATR3 8 , nonsense-mediated decay protein UPF1 9 , and RNA helicases DDX1 and MOV10 10 , 11 . Following nuclear export, the unspliced transcript can be incorporated into a variety of ribonucleoprotein complexes (RNPs).…”
Section: Introductionmentioning
confidence: 99%
“…In unresolved controversy, independent research identified siRNA downregulation of endogenous MOV10 did not change virion production and considered endogenous MOV10 acts as cofactor (Arjan-Odedra et al, 2012). In aggregate, modulation of MOV10 incurs an imbalance in HIV RNP activity, consistent with indirect and possibly beneficial effect on biogenesis of infectious HIV (Huang et al, 2015).…”
Section: Mov10 Activity In Virions Remains Undefinedmentioning
confidence: 53%